Voltage-mode first-order allpass filter using single-ended OTAs and grounded capacitor - Kumngern, Montree; Chanwutitum, Jirasak (My University, 2012)
This paper presents a new electronically tunable voltage-mode first-order allpass filter using only three single-ended operational transconductance amplifiers (OTAs) and one grounded capacitor, which is highly suitable for integrated circuit implementation. The pole frequency of the filter can be tuned electronically by adjusting the transconductance value of the OTA. No component-matching conditions are also required for realizing allpass response. The characteristics of the proposed circuit are simulated using PSPICE simulations to confirm the theory. © 2012 IEEE.
Keywords: allpass filter; analog signal processing; operational transconductance amplifier; voltage-mode circuit